2019
DOI: 10.1523/jneurosci.0524-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase 2 Potentiates Amyloid Deposition but Protects against Hippocampal Volume Loss and Demyelination in a Mouse Model of Alzheimer's Disease

Abstract: Sphingosine 1-phosphate (S1P) is a potent vasculoprotective and neuroprotective signaling lipid, synthesized primarily by sphingosine kinase 2 (SK2) in the brain. We have reported pronounced loss of S1P and SK2 activity early in Alzheimer's disease (AD) pathogenesis, and an inverse correlation between hippocampal S1P levels and age in females, leading us to speculate that loss of S1P is a sensitizing influence for AD. Paradoxically, SK2 was reported to mediate amyloid ␤ (A␤) formation from amyloid precursor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 83 publications
(117 reference statements)
0
19
0
Order By: Relevance
“…We have previously reported the loss of S1P and SphK2 activity early in the pathogenesis of Alzheimer's disease [23], and recently demonstrated that loss of SphK2 sensitizes to hippocampal atrophy and myelin loss in a mouse model of Alzheimer's disease [24]. We have also shown heightened anxiety in mice lacking SphK2 [25].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…We have previously reported the loss of S1P and SphK2 activity early in the pathogenesis of Alzheimer's disease [23], and recently demonstrated that loss of SphK2 sensitizes to hippocampal atrophy and myelin loss in a mouse model of Alzheimer's disease [24]. We have also shown heightened anxiety in mice lacking SphK2 [25].…”
Section: Introductionmentioning
confidence: 80%
“…The brain is enriched with sphingolipids, so an increased proportion of d18:2 (4,14) sphingolipids may have important consequences for neuronal lipid domains and myelin integrity. We have reported that SphK2 deficiency synergizes with an amyloid-producing transgene to create severe myelin deficits [24]. It is possible that myelin structure and function is destabilized by an increased abundance of sphingadiene lipids in SphK2 −/− mice, and this should be investigated in future studies, potentially by crossing SphK2 −/− to FADS3 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, STAT3 has been shown to promote the activation of sphingosine kinases and the production of sphingosine 1 phosphate (S1P) in inflammation related pathways in cancer [35]. In the context of AD, the loss of sphingosine kinase 2 activity and SP1 production are key pathogenic drivers of Aβ-mediated neurodegeneration [36]. Another upregulated pathway of interest is PI3K-AKT signaling, which has been extensively implicated in the pathogenesis of AD given its crucial role mediating insulin effects in the brain and other functions in microglia and astrocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, the discrepancies between different studies on changes in SL metabolism in AD are remarkable ( Crivelli et al, 2020 ). Intriguingly, studies on sphingosine-kinase and sphingosine-degrading enzymes have shown that lowering S1P decreases the Aβ production in vitro and in vivo ( Takasugi et al, 2011 ; Karaca et al, 2014 ; Lei et al, 2019 ). In addition, the relation between tau and the SL metabolism is poorly characterized, and there is no evidence of the implication of these lipids in its regulation.…”
Section: Introductionmentioning
confidence: 99%